Reservoirs of resistance: polymyxin resistance in veterinary‐associated companion animal isolates of Pseudomonas aeruginosa. (17th August 2019) - Scott, Andrea; Pottenger, Sian; Timofte, Dorina; Moore, Matthew; Wright, Laura; Kukavica‐Ibrulj, Irena; Jeukens, Julie; Levesque, Roger C; Freschi, Luca; Pinchbeck, Gina L; Schmidt, Vanessa M; McEwan, Neil; et al.
Abstract : Background: Pseudomonas aeruginosa is an opportunistic pathogen and a major cause of infections. Widespread resistance in human infections are increasing the use of last resort antimicrobials such as polymyxins. However, these have been used for decades in veterinary medicine. Companion animals are an understudied source of antimicrobial resistant P. aeruginosa isolates. This study evaluated the susceptibility of P. aeruginosa veterinary isolates to polymyxins to determine whether the veterinary niche represents a potential reservoir of resistance genes for pathogenic bacteria in both animals and humans. Methods and results: Clinical P. aeruginosa isolates (n=24) from UK companion animals were compared for antimicrobial susceptibility to a panel of human‐associated isolates (n=37). Minimum inhibitory concentration (MIC) values for polymyxin B and colistin in the companion animals was significantly higher than in human isolates (P=0.033 and P=0.013,  respectively). Genotyping revealed that the veterinary isolates were spread throughout the P. aeruginosa population, with shared array types from human infections such as keratitis and respiratory infections, suggesting the potential for zoonotic transmission. Whole genome sequencing revealed mutations in genes associated with polymyxin resistance and other antimicrobial resistance‐related genes. Conclusion: The high levels of resistance to polymyxin shown here, along with genetic similarities between some human and animal isolates, together suggest a need for sustained surveillance of this veterinary niche as a potential reservoir for resistant, clinically relevant bacteria in both animals and humans.